International legal protection of the marine environment from pollution from ships on the example of the Black Sea - Olena, Kostyria; Ivanova, A. V.; Костиря, О. В.; Костыря, Е. В.; Іванова, А. В.; Иванова, А. В. (Одеса : Видавничий дім «Гельветика», 2020)
The article is devoted to the research of the protection features of the Black Sea from pollution as a special area of the sea. There are determined pollution categories during the operation of ships (during the implementation of maritime activities on the seabed; caused by port activities, shipbuilding and ship’s repairing activities; the ingress of alien species or genetically modified organisms into the marine environment; the release of garbage, food, household and operational wastes into the sea; as a result of emergency circumstances – during accidents; and, pollution resulting from the burial of ships at sea). The international legal framework for the protection of the Black Sea marine environment from pollution during the operation of ships was analyzed. The universal and regional levels of legal regulation of the prevention of marine pollution from ships during their operation are highlighted. Particular attention is paid to the status of the Black Sea as a special area and a particularly vulnerable sea area. The Black Sea was defined as a “special area” of the sea, which is considered so vulnerable to oil pollution that discharges within it were completely prohibited with a few and clearly defined exceptions. To do this, we should refer to the provisions of the 1982 UN Convention on the Law of the Sea, which shares the powers of states in the protection of the marine environment from pollution from ships to the adoption of laws and regulations aimed at protecting the marine environment from pollution from ships, and regarding the enforcement of national laws and regulations, as well as international norms and standards for the prevention of marine pollution from ships. The scope of these powers of states is differentiated depending on the rules for which the marine zone is established, and also on the basis of who takes measures to ensure compliance with the rules and regulations. It is emphasized that in their inland waters and the waters of ports, states have full sovereignty and can establish special requirements related to the reduction, control and prevention of marine pollution, which foreign vessels must satisfy in order to enter and stay in these waters. It is noted that in order to increase the effectiveness of all measures to protect the marine environment from pollution from ships, it is necessary to clearly define the binding standards, that is, those that are international, the observance of which states under whose flag the vessels fly, as well as coastal countries, may require vessels located in their territorial waters or exclusive economic zone. Статтю присвячено дослідженню особливостей міжнародно-правового регулювання у сфері захисту Чорного моря від забруднення як особливого району моря. Визначено категорії забруднювачів моря при експлуатації суден (спричинене торговельним судноплавством, спричинене введенням у морське середовище немісцевих видів або генетично змінених організмів, забруднення при здійсненні морегосподарської діяльності на морському дні та портової діяльності; спричинене викидами у море сміття, харчових, побутових та експлуатаційних відходів; спричинене в результаті надзвичайних обставин, зокрема, при аваріях; спричинене похованням у морському середовищі) та проведено їх класифікацію. Проаналізовано міжнародно-правові основи забезпечення захисту морського середовища Чорного моря від забруднення з суден. Визначаються універсальний і регіональний рівні правового регулювання попередження забруднення морського середовища з суден. Особливої уваги приділяється статусу Чорного моря як “особливого району” і особливо вразливого морського району, яке вважається настільки вразливим до забруднення нафтою, шкідливими речовинами та сміттям, що викиди у його межах були повністю заборонені з невеликими і чітко визначеними виключеннями. Зазначається, що у своїх внутрішніх водах держави мають повний суверенітет і можуть встановлювати особливі вимоги, пов’язані зі скороченням, контролем і запобіганням забрудненню морського середовища, яким повинні задовольняти іноземні судна для можливого заходження та знаходження у цих водах. Визначено, що для підвищення ефективності усіх заходів для захисту морського середовища від забруднення з суден, необхідно визначити міжнародні норми, дотримання яких прибережні країни, можуть вимагати від суден, які знаходяться у межах їх територіальних морів та виключних економічних зон.
Міжнародно-правовий захист морського сере- довища від забруднення з суден на прикладі Чорного моря
Kostyria O., Ivanova A. International legal protection of the marine environment from pollution from ships on the example of the Black Sea / O. Kostyria, A. Ivanova // Lex Portus : юрид. наук. журн. / редкол. : С. В. Ківалов (голов. ред. ради), Б. А. Кормич (голов. ред.), Т. В. Аверочкіна (наук. ред., відп. секр.) [та ін.] ; НУ "ОЮА", ГО "МА “Святий Миколай". - Одеса : Видавничий дім «Гельветика», 2020. - № 1. – C. 37 - 50.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; international legal regulation; pollution from ships; special area; especially vulnerable marine area; protection of the marine environment of the Black Sea; міжнародно-правове регулювання; забруднення з суден; особливо вразливий морський район; захист морського середовища Чорного моря; загрязнение с судов; особенно уязвимый морской район; защита морской среды Черного моря